Profile of the Problem-Based Learning Model Assisted by E-THERM to Strengthen Students’ Problem-Solving Skills in Support of SDG 4: Quality Education - Nofri Hidayatin; Nurul Muawiyah; Siska Agustin Sha Hareni; Elvia Reza Lutfiani; Dhea Wanda Irani; Binar Kurnia Prahani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The purpose of this study is to analyze the problem-solving abilities of 11th-grade students at State Senior High School 1 Sidoarjo on the topic of temperature and heat as a foundation for implementing a digital book-assisted Problem-Based Learning (PBL) model. Method: This study employed a descriptive quantitative approach in the form of preliminary research involving 105 students selected through purposive sampling. Data were collected using essay tests based on Heller’s five problem-solving indicators, a Likert-scale questionnaire, and teacher interviews, and were analyzed descriptively to examine students’ initial abilities and readiness for digital book-assisted PBL implementation. Results: The findings show that 62.9% of students were categorized as having fair problem-solving abilities, 32.4% were in the poor category, and no students reached the good or very good categories. The physics description indicator was the most mastered aspect, while students’ abilities declined starting from the plan-a-solution indicator, indicating difficulties in systematically applying physics concepts to problem-solving. Novelty: This study provides empirical evidence on students’ readiness for implementing a digital book-assisted PBL model in physics learning, highlighting specific weaknesses in problem-solving indicators that can be addressed through the integration of digital learning resources within the PBL framework.